The role of orthographic and phonological processing during reading Chinese sentences: Evidence from eye movements - Lijuan, Zhang; Yingying, Zhang; Zhiwei, Liu; Lin, Li; Sha, Li; Jingxin, Wang (Frontiers in Psychology, 2023)
The role of phonological and orthographic processing and their time course during lexical processing and sentence reading remain controversial. By adopting a misspelled-characters disruption paradigm and eye-tracking technique, we manipulated the writing for the first characters of two-character target words to investigate the relative role of orthographic and phonological processing on word recognition in Chinese reading. There are four conditions: (a) correct character, (b) misspelled character with a stroke missing, (c) misspelled homographic character, and (d) misspelled homophonic character. The results showed that homophonic errors caused more disruptions than other conditions in the early (first-pass reading times) and later (total reading time) stages of lexical processing during Chinese reading. Homographic errors and omitted stroke errors lead to equal disruptions at the early stage of word recognition, but homographic errors cause more disruptions at the later stage. These results suggest that orthography plays a dominant role in word recognition during Chinese reading, whereas phonology plays a weaker and more limited role. The direct access and dual-rote hypothesis may well explain the mechanism of lexical processing in Chinese reading.